2017
DOI: 10.1097/mao.0000000000001617
|View full text |Cite
|
Sign up to set email alerts
|

The Etiological Relationship Between Migraine and Sudden Hearing Loss

Abstract: SSNHL patients had a higher prevalence of migraine. Although those with migraine had higher recovery rates, the differences were not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…There are a number of studies that described fluctuating or permanent SSNHL in patients with migraine. In other words, migraine has been found to be a risk factor of sudden deafness [Viirre et al, 1996;Evans et al, 2009;Arslan et al, 2017;Hwang et al, 2018;Kim et al, 2019]. A population-based cohort study conducted in the Re-public of Korea, which included 44,714 individuals, showed that the risk of development of SSNHL in patients with migraine was 1.34 times higher than in controls [Bolay et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a number of studies that described fluctuating or permanent SSNHL in patients with migraine. In other words, migraine has been found to be a risk factor of sudden deafness [Viirre et al, 1996;Evans et al, 2009;Arslan et al, 2017;Hwang et al, 2018;Kim et al, 2019]. A population-based cohort study conducted in the Re-public of Korea, which included 44,714 individuals, showed that the risk of development of SSNHL in patients with migraine was 1.34 times higher than in controls [Bolay et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…(1) The most accepted theory is based on the vascular mechanism of migraine. Vasospasms associated with migraine in small arterioles within the cochlea and labyrinth can induce the ELH [Radtke et al, 2012;Blödow et al, 2014;Arslan et al, 2017;Kırkım et al, 2017]. (2) Some inflammations and neurotransmitters involved in the pathogenesis of migraine affect the inner ear and the central auditory system [Balaban, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,14,15 There have also been nationwide population-based and prospective cohort studies suggesting that migraine, a complex neurovascular disorder, can increase the risk for developing SSNHL. [16][17][18] Thus, we present an investigation to evaluate the efficacy of supplementing IT steroid injection with migraine medications in improving SSNHL treatment outcome.…”
Section: Introductionmentioning
confidence: 99%